Analysis Of Baby Incubator Humidity Based PID with Kangaroo Mode - Singgih Yudha Setiawan; Dwi Herry Andayani; Andjar Pudji; Liliek Soetjiatie; Alievya Brillianty Anugrah Kusuma (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
The main factor that affects the parameters of the workings of humidity in the baby incubator is the sensor used to read the humidity in the room. The purpose of this study is to analyze the humidity sensor in the baby incubator using 2 humidity sensors (DHT11 and DHT22) in the different location. The manufacture of this device used an after-only design, with a comparison device of INCU Analyzer, DHT11, and DHT22 sensors. Based on the measurement, DHT11 produced a value of 46%, while DHT22 produced a value of 55.45% with BPFK standards of 50%-70%. Based on the results of measurements using the INCU Analyzer, the average error value for DHT11 is 16.05%, while DHT22 is 3.47%. Therefore, the results showed that the DHT22 sensor was more accurate to be used in baby incubators because the measurement results were under BPFK standards and produced a low error value. This can be further implemented in a baby incubator making to improve the health and safety of the babies